A Virus-Like Particle Vaccine Elicits Broad Neutralizing Antibody Responses in Humans to All Chikungunya Virus Genotypes. (21st September 2016) - Goo, Leslie; Dowd, Kimberly A.; Lin, Tsai-Yu; Mascola, John R.; Graham, Barney S.; Ledgerwood, Julie E.; Pierson, Theodore C.
Abstract: Chikungunya virus (CHIKV) is an alphavirus that has emerged as a global health burden. There are 3 CHIKV genotypes: Asian, West African, and Eastern/Central/South African. No licensed CHIKV vaccine is available, and whether the antibody response elicited by one genotype can neutralize heterologous genotypes is unclear. We assessed neutralizing antibody (NAb) responses of volunteers in a phase 1 study of a CHIKV vaccine against 9 viral strains representing all 3 genotypes. Minimal differences in vaccine-elicited NAb responses were observed among genotypes, suggesting that vaccination with a single CHIKV strain can elicit cross-protective NAbs against all 3 genotypes.